2013
DOI: 10.1038/srep03453
|View full text |Cite
|
Sign up to set email alerts
|

Tactile stimulation can suppress visual perception

Abstract: An input (e.g., airplane takeoff sound) to a sensory modality can suppress the percept of another input (e.g., talking voices of neighbors) of the same modality. This perceptual suppression effect is evidence that neural responses to different inputs closely interact with each other in the brain. While recent studies suggest that close interactions also occur across sensory modalities, crossmodal perceptual suppression effect has not yet been reported. Here, we demonstrate that tactile stimulation can suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…Recently, tactile suppressive effects on visual perception were also reported (touch-induced visual suppression; TIVS)20. This study showed that a tactile vibration degraded orientation discrimination performance for visual stimuli.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…Recently, tactile suppressive effects on visual perception were also reported (touch-induced visual suppression; TIVS)20. This study showed that a tactile vibration degraded orientation discrimination performance for visual stimuli.…”
mentioning
confidence: 52%
“…In the next main session, we presented the targets for each participant with the estimated spatial frequency value at the left or right of the fixation point. After 50 ms, a vibration (200 Hz sinusoidal burst) was applied to the participants’ left index finger for 200 ms in order to effectively induce TIVS20. The participants were asked to make visual orientation judgments while ignoring the tactile stimulus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations